Assessing Livelihood Capitals on Vashantek Slum and its Impact on Adjacent Communities - Rokoni, Sumaiya; Rahman, Md. Mizanur (The Jahangirnagar Review, 2024)
Livelihoods are people's pattern of living or practices that involve the use of resources to support the essential needs of the household. According to the Sustainable Livelihood Framework provided by UK’s Department for International Development (DFID), there are five capitals of livelihood defined as the ‘livelihood assets’ which influences people in every aspect of life from their household level. The five capitals of livelihood include- human capital, physical capital, financial capital, social capital and natural capital. The livelihood practices of the low income people who live in the slums are immensely influenced by these 5 capitals; and such livelihood condition also impacts its adjacent communities as well. This study especially focuses on the case of Vashantek slum of Dhaka city in order to provide a precise understanding of the livelihood capitals possessed by the slum households. This research tries to find out the availability and accessibility of the five livelihood capitals on Vashantek slum. This study also tries to demonstrate how the livelihood activities of slum people are affecting the surrounding high-class and middle-class communities. Both qualitative and quantitative data have been obtained from field survey to conduct the research. The collected data and information are analyzed through statistical, narrative and descriptive analysis methods and finally an assessment has been represented through grounded-theory approach. This study shows a very vulnerable condition of the slum livelihood; and the availability and accessibility of livelihood capitals are not sufficient among the slum neighborhoods. Sustainable livelihood framework (SLF) can broadly be applied and experimented here for the improvement of the livelihood capitals of Vashantek slum and its surroundings. Based on the findings, this research recommends some short-term and long-term strategies along-with every stakeholder’s role to improve the condition of this slum-livelihood.